Accommodation at the club - Mumbai Archive Project (Jio Institute, 2024)
Accommodation at the club is cheap but basic. Guests are provided a single bed in the dormitory. Only members of the club are allowed to stay in dormitories. Those who are not members stay in the adjacent building as tenants. Unlike a hotel, there are no hard-and-fast rules for guests. However, every guest is expected to maintain decorum and discipline and not create nuisances for others.